2021
DOI: 10.1186/s12967-021-02998-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lncRNA-miRNA-mRNA expression pattern in heart tissue after total body radiation in a mouse model

Abstract: Background Radiation therapy is integral to effective thoracic cancer treatments, but its application is limited by sensitivity of critical organs such as the heart. The impacts of acute radiation-induced damage and its chronic effects on normal heart cells are highly relevant in radiotherapy with increasing lifespans of patients. Biomarkers for normal tissue damage after radiation exposure, whether accidental or therapeutic, are being studied as indicators of both acute and delayed effects. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 139 publications
(119 reference statements)
1
9
0
Order By: Relevance
“…All three have previously been highlighted as predictive markers of radiation injury in murine models 38 , 58 61 . Cdkn1a has previously been reported as a marker of irradiation in cancer patients undergoing WBI and in murine models from our lab and others 25 , 35 , 62 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…All three have previously been highlighted as predictive markers of radiation injury in murine models 38 , 58 61 . Cdkn1a has previously been reported as a marker of irradiation in cancer patients undergoing WBI and in murine models from our lab and others 25 , 35 , 62 .…”
Section: Discussionmentioning
confidence: 69%
“…Research from our lab and others have highlighted the radiation response of multiple lncRNA. Some of these lncRNA are otherwise uncharacterized, while others, such as Trp53cor1 and Dino , are relatively well known 25 28 . MicroRNA (miRNA), non-coding RNA of roughly 22 nucleotides, exert their functions by hybridizing to complementary sequences in the 3’ UTRs of mRNAs, which lead to either RNA degradation or translation inhibition 29 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study screened mouse cardiac tissue for the changes in mRNAs, miRNAs, and lncRNAs levels that predict radiation-induced heart damage after exposing mice to 1, 2, 4, 8, and 12 Gray (Gy) whole-body irradiation for 48 h ( 177 ). The study found that the expression alterations in numerous mRNAs and ncRNAs at different doses, such as LncRNA Abhd11os, Pvt1, Trp53cor1, and Dino, rose as the radiation dose increased.…”
Section: Ncrnas As Biomarkers In Cancer Therapy-induced Cardiotoxicitymentioning
confidence: 99%
“…However, despite decades of research, a gap in this field remains. Biological molecules that have been pursued include DNA [ 2 , 3 ], multiple species of RNA such as long non-coding RNA (lncRNA) [ 4 ], miRNA [ 5 , 6 ], mRNA [ 4 , 7 ], proteins and protein arrays [ 8 , 9 , 10 ], advanced multi-omic platforms [ 11 ] and others [ 12 ]. Essential to bridging this gap is establishing representative animal models and conducting relevant clinical trials.…”
Section: Introductionmentioning
confidence: 99%